2019
DOI: 10.1136/postgradmedj-2019-136684
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of long non-coding RNA 01296 expression in human solid malignant tumours: a meta-analysis

Abstract: Long intergenic non-coding RNA 01296 (LINC01296) has been reported to play an important role in many human malignancies, but a consistent perspective has not been established now. To explore the prognostic value of LINC01296 in different types of human solid malignant tumours, we performed this meta-analysis.An electronic search of PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure, Cochrane Library, Chinese Biological Medical Literature database and WanFang database was applied to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Nowadays, increasing researches have reported that a number of lncRNAs might play multiple functions in the initiation and progression of CMM [ 15 , 16 ]. LINC01296 was found to be aberrantly expressed in several malignancies, including hepatocellular carcinoma, osteosarcoma and oral squamous cell carcinoma, and LINC01296 could also regulate tumorigenesis and progression of cancers [ 17 ]. We also observed aberrant expression of LINC01296 in CMM by GEPIA data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, increasing researches have reported that a number of lncRNAs might play multiple functions in the initiation and progression of CMM [ 15 , 16 ]. LINC01296 was found to be aberrantly expressed in several malignancies, including hepatocellular carcinoma, osteosarcoma and oral squamous cell carcinoma, and LINC01296 could also regulate tumorigenesis and progression of cancers [ 17 ]. We also observed aberrant expression of LINC01296 in CMM by GEPIA data analysis.…”
Section: Introductionmentioning
confidence: 99%